Prediction of serum NGAL levels using comorbidity AHEAD score and two-year prognosis in stable chronic heart failure patients (FAR NHL registry). (25th November 2020) - Labr, K; Spinar, J; Parenica, J; Spinarova, L; Malek, F; Spinarova, M; Ludka, O; Jarkovsky, J; Benesova, K; Pavkova Goldbergova, M; Labrova, R
Abstract: Background: Neutrophil gelatinase-associated lipocalin (NGAL) is marker of renal function and is strongly associated with presence of comorbidities. AHEAD comorbidity score is commonly used to predict survival in acute heart failure patients and could predict events even in chronic heart failure. Methods: 547 stable patients with chronic heart failure patients with left ventricular ejection fraction <50% were included in FARmacology and NeuroHumoraL activation (FAR NHL) registry. Three cardiological centres from The Czech Republic with speciality in heart failure were participating. Results: Median age was 66 years, 80.3% were men. The etiology of heart failure was in 54% ischemic heart disease, in 40% dilatated cardiomyopathy, in 0.5% hypertrophic cardiomyopathy. 60% of patients were in NYHA class II. In the first two years of follow-up, 74 events (13.5%) occurred, including all-cause death, left ventricle assist device implantation or orthotopic heart transplantation. The AHEAD comorbidity score (Atrial fibrillation, low Haemoglobin level <120 g/L in female or <130 g/L in male, Elderly >70 years; Abnormal renal parameters with creatinine >130 μmol/L, Diabetes mellitus; 1 point for each comorbidity present) was set in this registry. Patients with AHEAD 0–1 survived without event in 89.2%, AHEAD 2–3 in 82.4% and AHEAD 4–5 only in 63.5% (p<0.001; pairwise comparison 0.034, <0.001, 0.021). Also levels of NGAL are higher when comorbidities from AHEAD score are present: Atrial fibrillation (62 vs. 50 ng/mL; p<0.001), Haemoglobin level (Spearman's rank correlation coefficient −0.240; p<0.001), Eldery (Spearman's coefficient 0.425; p<0.001), Abnormal creatinine level (Spearman's coefficient 0.528; p<0.001), Diabetes mellitus (57 vs. 51 ng/mL; p=0.006). NGAL levels are singificantly higher in patients with higher AHEAD score. Mean level of NGAL in AHEAD 0–1 (N=320) is 51 ng/mL, in AHEAD 2–3 (N=190) is 78 ng/mL and in AHEAD 4–5 (N=37) is 142 ng/mL (Kruskal-Wallis test p<0.001, pairwise comparision all <0.001). Conclusion: In stable chronic heart failure registry FAR NHL, comorbidity score AHEAD can predict events. Serum NGAL level is significantly higher when AHEAD score comorbidities are present: Atrial fibrillation, low Haemoglobin, Eldery, Abnormal renal function and Diabetes mellitus. Funding Acknowledgement: Type of funding source: None